Constitutional Court statistics for the 2013 term. Issue 1 (2nd January 2016) - Wentzel, Marie; Viljoen, Johan; Samaradiwakera-Wijesundara, Charmika; Cooke, Marc; Ndebele, Cebile; Koitsioe, Basetsana; Jones, Tristan; Chamberlain, Lisa
Abstract: This note provides descriptive statistics on the work of the Constitutional Court of South Africa in 2013, organised in a number of tables. Part I covers those decisions in which the Court produced a written judgment while Part II covers applications that were considered in chambers and dismissed without a judgment being given. The purpose of the Constitutional Court statistics is to shed light on issues such as voting patterns on the bench, the nature of cases heard by the Court, government success rates in Constitutional Court litigation, how cases are reaching the Court, and how long it is taking the Court to deliver its judgments. The statistics also provide some insight into the applications that are not being heard by the Court, which are otherwise not open to public scrutiny.